Can We Produce True Seed of Shallot (TSS) from Small Size Shallot Sets? - Palupi, Endah R.; Manik, Fatiani; Suhartanto, M Rahmad (Journal of Tropical Crop Science, 2017)
The Indonesian government has been promoting the use of true seed of shallot (TSS) for shallot production due to its higher productivity potentials and greatly reduced risk of disease transfer. This research was conducted at Leuwikopo experimental station, Department of Agronomy and Horticulture, Bogor Agricultural University, West Java, Indonesia, in 2015. The aim of the research was to study TSS production from small size shallot sets “Bima Brebes”, an easy to flower shallot cultivar.  The trial was arranged in a completely randomized block design with two factors; BAP concentration i.e. 50, 100 150, 200 ppm as the first factor and the sizes of mother bulbs, i.e. small (3-4 g) and medium (5-10 g), as the second factor. The results showed that the vegetative growth of plants from the two bulb sizes were similar. TSS production and TSS quality from small size (3-4 g) bulbs was also comparable to that of medium size shallot set, except for 1000 seeds weight in which medium size mother bulb produced heavier 1000-seeds weight than that of small size shallot set. Therefore small size shallot set can potentially be useful for TSS production.